Estimation of shortwave direct aerosol radiative forcing at four locations on the Indo-Gangetic plains: Model results and ground measurement. (August 2017) - Bibi, Humera; Alam, Khan; Bibi, Samina
Abstract: This study provides observational results of aerosol optical and radiative characteristics over four locations in IGP. Spectral variation of Aerosol Optical Depth (AOD), Single Scattering Albedo (SSA) and Asymmetry Parameter (AP) were analysed using AErosol RObotic NETwork (AERONET) data. The analysis revealed that coarse particles were dominant in summer and pre-monsoon, while fine particles were more pronounced in winter and post-monsoon. Furthermore, the spatio-temporal variations of Shortwave Direct Aerosol Radiative Forcing (SDARF) and Shortwave Direct Aerosol Radiative Forcing Efficiency (SDARFE) at the Top Of Atmosphere (TOA), SURface (SUR) and within ATMosphere (ATM) were calculated using SBDART model. The atmospheric Heating Rate (HR) associated with SDARFATM were also computed. It was observed that the monthly averaged SDARFTOA and SDARFSUR were found to be negative leading to positive SDARFATM during all the months over all sites. The increments in net atmospheric forcing lead to maximum HR in November–December and May. The seasonal analysis of SDARF revealed that SDARFTOA and SDARFSUR were negative during all seasons. The SW atmospheric absorption translates to highest atmospheric HR during summer over Karachi and during pre-monsoon over Lahore, Jaipur and Kanpur. Like SDARF, the monthly and seasonal variations of SDARFETOA and SDARFESUR were found to be negative, resulting in positive atmospheric forcing. Additionally, to compare the model estimated forcing against AERONET derived forcing, the regression analysis of AERONET-SBDART forcing were carried out. It was observed that SDARF at SUR and TOA showed relatively higher correlation over Lahore, moderate over Jaipur and Kanpur and lower over Karachi. Finally, the analysis of National Oceanic and Atmospheric Administration Hybrid Single Particle Lagrangian Integrated Trajectory (HYSPLIT) model revealed that air masses were arriving from multiple source locations. Highlights: The spectral behavior of AOD, SSA and AP were analysed. SDARF showed significant monthly, seasonal & annual variations at TOA, SUR & ATM. Positive atmospheric forcing leads to the warming effect in lower atmosphere. Model estimated and AERONET derived SDARF were in good agreement. The HYSPLIT trajectories were originating from multiple source locations.